Comparison of Bilateral Infraorbital Nerve Block with Lidocaine Hydrochloride (Xylocaine) Or Bupivacaine Hydrochloride (Marcaine) With Intravenous Pethidine for Postoperative Pain Management of Pediatric Patients of Cleft Lip Surgery (Cheiloplasty): A Prospective Double Blind Randomized Clinical Trial - Mahdavi, Alireza; shahabi, Farnaz; Eghbali Zarch, Ahmad; Razavi, Sajad; Khaleghnejad tabari, Ahmad; Mahdavi , Nastaran; Ahmadi Zadeh, Narjes; Kalantar, Jalil (Iranian Journal of Pediatric Surgery, 2024)
Introduction: Post-operative pain relief is one of the major practices in anesthesiology. The different pharmacokinetic and sensitivity of children to different classes of anesthetics drugs, especially opioids, make the clinical judgment of pediatric anesthesiologist harder. Materials and Methods: After getting ethical approval, all the patients who underwent surgery for cleft lip surgery with pain management at Mofid Children’s Hospital were contacted, and in case of any long-term complications, parents were invited to visit the hospital. Results: The average duration of analgesia in the X, M and P group were 18.48± 2.45, 17.62± 2.96, and 17.56± 3.16 hours, respectively. The duration of analgesia in the group X was superior to the other groups; however, there was not any meaningful different between the duration of analgesia between the 3 groups (p>0.05). Conclusion: the present double-blind clinical trial disclosed that the preoperative bilateral infraorbital nerve block induced an anesthetic effect prolonged as the duration induced by the opioid infusion.